Адсорбція хітозану на поверхні змішаних оксидів - Borodavka, T. V.; Palyanytsya, B. B.; Kulik, T. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
The adsorption isotherms of chitosan on silica, silica-titania and silica-alumina have surfaces been obtained. The adsorption capability was found to decrease in the row silica-alumina>silica-titania> silica. Chitosan modified oxides have been examined by the temperature-programmed desorption mass spectrometry method. The low-temperature peaks of the thermo-desorption curves of chitosan destruction occur for silica-titania and silica-alumina as well as for individual silica. These low-temperature maxima correspond to the thermolysis of trains of adsorbed polymer. Thermolysis of chitosan on silica-titania and silica-alumina has been shown to realize with deep destruction of pyranosic rings and breaking of C–C bonds in contrast to thermolysis of chitosan on silica surface.